ВЗАЄМОДІЯ ІНСТИТУТІВ СПІЛЬНОГО ІНВЕСТУВАННЯ З БАНКІВСЬКИМИ УСТАНОВАМИ НА ФІНАНСОВОМУ РИНКУ (Світ фінансів, 2017)
Письменна Т. М. Взаємодія інститутів спільного інвестування з банківськими установами на фінансовому ринку. Висвітлено питання конкуренції і взаємодії інститутів спільного інвестування (далі ІСІ) та банківських установ. Розглянуто особливості щодо перерозподілу сфер впливу на фінансовому ринку України між фінансовими посередниками залежно від запропонованих пріоритетів. Показано можливості співпраці ІСІ та банківських установ. Наведено зарубіжний досвід такої взаємодії. Pysmenna I. Cooperation between joint investment institutes and banking institutions at the financial market. The issues concerning competition and cooperation of joint investment institutes and banking institutions are considered. The peculiarities being developed in the financial market of Ukraine regarding distribution of influence spheres between financial intermediaries depending on the offered priorities are revealed. The opportunities of cooperation between joint investment institutes and banks are proved. Such cooperation experience of foreign countries is given.